2006
DOI: 10.1007/s10591-006-9693-4
|View full text |Cite
|
Sign up to set email alerts
|

Work and Family Conflict: An Often Overlooked Issue in Couple and Family Therapy

Abstract: Despite the systemic interaction, family-based journals, as well as intake and assessment forms most frequently used by couple and family therapists (CFTs), have given a limited amount of attention to the issue of work and family conflict. Moreover, a review of the literature indicated that many CFTs perceive themselves as inadequately prepared to assist couples and families with work and family conflict. Addressing this apparent limitation, the present study identified various work stressors that contributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…While the purpose of therapy and work–life are different, previous researchers demonstrated that therapy can assist employees to resolve their work–family conflict, thus ensuring that employees are satisfied on both fronts (cf. Carroll et al, 2013; Frone et al, 1992; Tatman et al, 2006). Similarly, in their study of transactive memory, Wegner et al (1991) have established the significance of intimate partner relationships in a work context.…”
Section: Methodsmentioning
confidence: 99%
“…While the purpose of therapy and work–life are different, previous researchers demonstrated that therapy can assist employees to resolve their work–family conflict, thus ensuring that employees are satisfied on both fronts (cf. Carroll et al, 2013; Frone et al, 1992; Tatman et al, 2006). Similarly, in their study of transactive memory, Wegner et al (1991) have established the significance of intimate partner relationships in a work context.…”
Section: Methodsmentioning
confidence: 99%
“…Not surprisingly, the experience of job stress has been found to reduce marital quality in both partners (Obradovic and Cudina-Obradovic, 2009). A majority of research in this domain has been conducted in the United States or with Western samples and has found that men were affected by work-family conflict as much as women, however, women were more likely to be affected by family-work conflict than men (e.g., Tatman et al, 2006). However, recent research is starting to examine these associations with non-Western samples.…”
Section: Introductionmentioning
confidence: 99%
“…Although several prior studies have highlighted the importance of family variables to explain family satisfaction (Olson, 2000), FWC (Greenhaus and Beutell, 1985;Kinnunen and Mauno, 1998;MacEwen and Barling, 1994;Michel, Kotrba, Michelson, Clark and Baltes, 2011;Netemeyer. Boles and McMurrian, 1996;Stephens, Townsend, Martire and Druley, 2001;Tatman, Hovestadt, Yelsma, Fenell and Canfield, 2006;Voydanoff, 1988) and WFC (Evenson and Simon, 2005;Kinnunen and Mauno, 1998;Nomaguchi and Milkie, 2003;Stephens, Townsend, Martire and Druley, 2001;Voydanoff, 1988), according to the results of this study, family cohesion increases family satisfaction since it contributes to less family interference in professional activity (i.e. FWC).…”
Section: Discussionmentioning
confidence: 50%